2021
DOI: 10.1155/2021/7056506
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel PPAR Signature for Predicting Prognosis, Immune Microenvironment, and Chemotherapy Response in Bladder Cancer

Abstract: Background. Mounting evidence has confirmed that peroxisome proliferator-activated receptors (PPARs) played a crucial role in the development and progression of bladder cancer (BLCA). The purpose of this study is to comprehensively investigate the function and prognostic value of PPAR-targeted genes in BLCA. Methods. The RNA sequencing data and clinical information of BLCA patients were acquired from The Cancer Genome Atlas (TCGA). The differentially expressed PPAR-targeted genes were investigated. Cox analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Fatty acid desaturase 2 (FADS2) could fix in fatty acyl chain to adjust unsaturated fatty acids through the introduction of a double bond between carbon. Zhu et al confirmed that FADS2 was correlated with immune infiltration of tumor cells through participation in peroxisome proliferator-activated receptors (PPARs) signaling through GSEA enrichment analysis (Zhu et al, 2021). Furthermore, interference with FADS2 expression could protect immortalized primary hepatocytes and lung cancer cells from erastin-induced ferroptosis.…”
Section: Discussionmentioning
confidence: 95%
“…Fatty acid desaturase 2 (FADS2) could fix in fatty acyl chain to adjust unsaturated fatty acids through the introduction of a double bond between carbon. Zhu et al confirmed that FADS2 was correlated with immune infiltration of tumor cells through participation in peroxisome proliferator-activated receptors (PPARs) signaling through GSEA enrichment analysis (Zhu et al, 2021). Furthermore, interference with FADS2 expression could protect immortalized primary hepatocytes and lung cancer cells from erastin-induced ferroptosis.…”
Section: Discussionmentioning
confidence: 95%
“…Through the results of Gene Ontology and KEGG enrichment analysis, FADS2 plays an oncogenic driver role by driving cancer cells proliferation, cell migration, and EMT through VEGF, MAPK, and PPAR pathways. An analysis of GSEA by Zhu K et al revealed that the PPAR signature correlated with the infiltration of tumor immune cells [ 21 ]. In a recent study, Mokhtari et al showed a cross-talk between the unsaturated fatty acid synthesis pathway and arachidonic acid metabolism and that the PPAR signaling pathway was regulated via these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The differential IC50 of chemotherapeutic agents between low and high FBN2 expression groups was predicted by the ‘pRRophetic’ package [ 35 ]. Based on gene expression microarray data, the pRRophetic package, which was used to determine IC50 with success in previous research [ 36 , 37 , 38 , 39 ], was performed for the prediction of clinical chemotherapeutic response by using statistical models from the gene expression and drug sensitivity data from cell lines in the Cancer Genome Project [ 40 ] as a training set.…”
Section: Methodsmentioning
confidence: 99%